The Contribution of Gut Microbiota–Brain Axis in the Development of Brain Disorders - Maiuolo, Jessica; Gliozzi, Micaela; Musolino, Vincenzo; Carresi, Cristina; Scarano, Federica; Nucera, Saverio; Scicchitano, Miriam; Oppedisano, Francesca; Bosco, Francesca; Ruga, Stefano; Zito, Maria Caterina; Macri, Roberta; et al. (Frontiers in Neuroscience, 2021)
Different bacterial families colonize the most part of mucosal tissues of our organism such as the skin, mouth, vagina, respiratory and gastro-intestinal districts. In particular, the mammalian intestine hosts a microbial community of about 1000-1500 bacterial species, collectively called “microbiota”. A co-metabolism between the microbiota and the host system is generated and the symbiotic relationship has been described as mutually beneficial. The balance that is achieved between the microbiota and the host organism is fundamental to the organization of the immune system. Scientific studies have highlighted a direct correlation between the intestinal microbiota and the brain, establishing the existence of the Gut Microbiota-Brain Axis. Based on this theory, the microbiota acts on the development, physiology, and cognitive functions of the brain, although the mechanisms involved have not yet been fully interpreted. Similarly, a close relationship between alteration of the intestinal microbiota and the onset of some neurological pathologies has been highlighted. This review aims to point out current literature knowledges about connection between intestinal dysbiosis and the onset of some neurological pathologies such as anxiety and depression, autism spectrum disorder and multiple sclerosis. These disorders have always been considered as a consequence of neuronal alterations, but in this review we hypothesized that they may have a non-neuronal origin: if the composition of the microbiota was directly involved? In this direction will be highlighted two key points: 1) the direct crosstalk between neurons and gut microbiota and 2) the impact level of the microbiota on the brain. If the hypothesis is confirmed, we could consider the microbiota a valuable target for reducing or modulating the incidence of some neurological diseases.